Relationship between 3D lower-limb kinematics and foot propulsive force during breaststroke kicking - Koga, D.; Tsunokawa, T.; Kawai, E.; Nakazono, Y.; Sengoku, Y.; Takagi, H. (Sports Biomechanics, 2026)
In breaststroke, leg kick propulsion plays a major role in swimming velocity; however, the relationship between propulsive force and its kinematics remains underexplored. This study aimed to identify leg movements that enhance foot propulsive force. Fourteen male swimmers performed 10 seconds of maximal-effort breaststroke kicks while holding a board with their upper limbs in a swimming flume. Leg kinematics and foot propulsive force were measured using a motion-capture system and eight pressure sensors on the left foot. During the knee extension phase, foot propulsive force correlated significantly with hip adduction/abduction range of motion (ROM) (r = -0.57), ankle plantar/dorsiflexion ROM (r = 0.59), mean plantar/dorsiflexion angular velocity (r = 0.56), peak knee extension angular velocity (r = -0.54), and peak ankle plantar flexion angular velocity (r = 0.59). In the insweep phase, foot propulsive force correlated significantly with foot resultant speed (r = 0.89), foot forward-backward velocity (r = 0.79), and foot vertical velocity (r = 0.71). This study suggests that during the knee extension phase, adjustments in ROM and increases in angular velocity of lower limb joints are associated with greater foot propulsive force, while higher foot velocity is associated with increased propulsive force during the insweep phase.